Implementation of servant leadership in profit and non-profit context: is it different? - Diah Astrini Amir; Claudius Budi Santoso; Rasistia Wisandianing Primadineska (Diponegoro International Journal of Business, 2021)
The purpose of this study is to examine the differences between servant leadership (SL) in the profit and non-profit organization sectors. This study also examines the effectiveness of SL on the subordinate performance in profit and non-profit organizations. A total of 254 subordinates from profit and non-profit organizations participated in this study. This study used non-probability sampling, purposive sampling technique. This study uses MANOVA to examine the differences between SL in profit and non-profit organizations and uses simple regression to examine the effect of SL on employee performance. The results of the study report that there are no significant differences between servant leadership in profit or non-profit organizations. Servant leadership also consistently has a positive and significant effect on subordinate Organizational Citizenship Behavior (OCB) for both profit and non-profit organizations. This research was measured using perceptions of subordinates and using a quantitative approach. The early emergence of SL was associated with religious organizations (non-profit) so that SL was attached to leadership that was more appropriate in non-profit organizations. However, some argue that SL effective in the profit organization sector. This study is expected to provide empirical evidence regarding the application of servant leadership in profit vs non-profit organizations in servant leadership studies.